Pemberdayaan Desa Juk Ayak Menuju Desa Maju - Maaruf, Medi Hendra; -, Heruddin; Prasetyo, Arif; Mbewu, Nur Inayah; Pratiwi, Aprilia A; Aminuddin, Din; -, Kristina; Dhiu, Waltrudis (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2023)
Juk Ayak is the largest and oldest village in Telen District, East Kutai Regency, East Kalimantan Province. The village is the capital city of the Telen District, however there is a little information about Juk Ayak village in today’s digital era. There are several problems faced by the village, some of them came from village administration, in terms of unclear village border, increasing of land opening for oil palm plantation development initiated by locals, ethics education, and less interest of mathematics in elementary school students. The applied method was initial observations together with village officials and the local community regarding the problems they faced. The next step was to identify problems and collect data on resource potential at the moment. Then, we discussed about possible best solutions by involving all parties as outlined in our planned work program. The result of activities and outcomes from the achieved work program were village website making, writing articles for website content, socializing the importance of protecting forest and land from fires, establishing a fire society care (MPA), designing village map, learning social ethics and the introduction of mathematics in interesting and fun way for kids.